Scenario- Based Learning Approach for Enhancing the Critical Thinking Skills of Grade 9 Students in Araling Panlipunan - Joaquin, Lyn L.; Hermosa, Jherwin P. (Future Science / FSH-PH Publications, 2023)
This study examined the efficacy of Scenario- Based Learning (SBL) Approach for enhancing the Critical thinking skills of Grade 9 students in Araling Panlipunan. Scenario- Based Learning Approach is a student centred approach in Araling Panlipunan and suited to the 21st century learners. Thus, this descriptive quasi-experimental research design determined the cause and effect of SBL approach to the critical thinking skills of 40 Grade 9 students of Col. Lauro D. Dizon Memorilal Integrated High School. The results were analysed using mean and standard deviation, t-test and Pearson-r correlation. The study revealed that using SBL approach, students can become more involved, motivated, and develop their real-world skills. Application of SBL approach had great impact in the learning process. Moreover, there was a significant difference in the responses of learners in the pre-test and posttest. It means that the quality and content of SBL approach has positive impact on the learning process in critical thinking skills. This approach become more effective in critical thinking skills as learners had been able to remember, reason and pay attention to SBL approach video lesson. In addition, usage of technology improved learning. The opportunities for teaching with audio visual lessons are ideally adapted to the learners’ environment. Thus, learning scenario encourages students to think about what they have learned.